2018
DOI: 10.14687/jhs.v15i3.5352
|View full text |Cite
|
Sign up to set email alerts
|

A research to examine general and decisional procrastination of healthcare workers according to differences of demographical characteristics

Abstract: In a world of rapid change and transformation, many developments in different fields have affected both the organization and the individual, and these changes have led to an increase in the number of stimulants affecting employees. One of the most intensive problems in this regard is the procrastination of employees. The aim of this research is to examine if there is a significant difference at the levels of general and decisional procrastination of employees in scope of demographic variables. In this context,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A study showed that decisional procrastination was at an average level in healthcare workers. [ 16 ] The prevalence of average and severe workplace procrastination among midwives in Iran is reported as 17.1% and 1.5%, respectively. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that decisional procrastination was at an average level in healthcare workers. [ 16 ] The prevalence of average and severe workplace procrastination among midwives in Iran is reported as 17.1% and 1.5%, respectively. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%